A novel approach to desalination: producing potable water from seawater - Farshad Farahbod (Applied Water Science)
Abstract Freshwater production systems aim to convert seawater into usable freshwater. Two primary methods are employed: 1. Distillation: This process involves heating seawater to vaporize it, leaving behind salts. The vapor is then condensed back into freshwater. 2. Membrane processes: These utilize semipermeable membranes to separate salt from water. Reverse osmosis is a common example, where pressure forces water molecules through the membrane while leaving salts behind. Optimizing these systems often involves: (1) Minimizing seawater intake: Reducing the amount of seawater needed for a given freshwater output is crucial. (2) Chemical use reduction: Chemicals are often used for cleaning membranes, preventing scaling, and controlling biofouling. This study proposes a novel approach for producing potable water by diluting desalinated seawater with the discharge water from the South Pars Gas Complex (SPGC) first refinery. This method focuses on creating a self-sustaining system for water production that is environmentally friendly and may even improve the quality of the water. The results were compared to established Iranian and international drinking water quality standards to assess the design’s efficiency. The proposed design incorporates the following treatment steps: (A) pre-treatment, (B) dilution, (C) pH and CO2 adjustment, (D) hardness removal, (E) secondary disinfection, (F) final polishing, (G) disinfectant injection and (H) distribution. Implementing this design has the potential to significantly reduce the consumption of sodium chloride salt (estimated at 67,000 kg) and carbon dioxide (estimated at 10,800 kg). Additionally, it might lead to a lower overall usage of calcium carbonate and sodium carbonate for pH and hardness adjustments.